2017
DOI: 10.1080/13510002.2017.1324381
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant properties of drugs used in Type 2 diabetes management: could they contribute to, confound or conceal effects of antioxidant therapy?

Abstract: Objectives: This is a narrative review, investigating the antioxidant properties of drugs used in the management of diabetes, and discusses whether these antioxidant effects contribute to, confound, or conceal the effects of antioxidant therapy. Methods: A systematic search for articles reporting trials, or observational studies on the antioxidant effect of drugs used in the treatment of diabetes in humans or animals was performed using Web of Science, PubMed, and Ovid. Data were extracted, including data on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 154 publications
1
34
0
Order By: Relevance
“…Diabetes mellitus is a complex metabolic disorder characterized by hyperglycemia, pancreatic beta (β) cells dysfunction, and abnormal lipid profile that result from metabolic deregulations, impaired insulin secretion and action, and inappropriate consumption of glucose [1]. It is one of the most prevalent chronic diseases and leads towards severe complications such as increase in production of reactive oxygen species (ROS), impairment of antioxidant enzymes [2], hyperglycemia [3], dislipidemia [4], alteration in insulin signaling pathway, and ROS-induced cellular damage [5]. All these changes will result in diabetes-associated secondary complications like nephropathy, retinopathy, neuropathy, and cardiovascular morbidity [6].…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes mellitus is a complex metabolic disorder characterized by hyperglycemia, pancreatic beta (β) cells dysfunction, and abnormal lipid profile that result from metabolic deregulations, impaired insulin secretion and action, and inappropriate consumption of glucose [1]. It is one of the most prevalent chronic diseases and leads towards severe complications such as increase in production of reactive oxygen species (ROS), impairment of antioxidant enzymes [2], hyperglycemia [3], dislipidemia [4], alteration in insulin signaling pathway, and ROS-induced cellular damage [5]. All these changes will result in diabetes-associated secondary complications like nephropathy, retinopathy, neuropathy, and cardiovascular morbidity [6].…”
Section: Introductionmentioning
confidence: 99%
“…Another study revealed that vitamins C and E are the most frequently administered antioxidants used as supplements in subjects with type 2 DM. They also noted that the supplementation period was between 3 and 12 weeks [407]. T2DM patients are more susceptible to micro-and macrovascular complications; thus, daily intake of vitamins as supplements offers a new approach for metabolic control, as well as summing up the effect of diet, exercise, and medication.…”
Section: Zaleya Decandramentioning
confidence: 99%
“…Several classes of approved drugs have been studied through the years for their antioxidant properties [ 1 , 5 , 6 ]. Proton pump inhibitors [ 7 ], antidiabetics [ 8 ], drugs acting on the cardiovascular system [ 9 ], antiepileptics [ 10 ], and anti-inflammatory agents [ 11 ] represent some of the investigated classes, which are also paired by antioxidant natural and semi-synthetic compounds with biological activity [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. Furthermore, besides therapeutic agents, it must be stressed that bioactive components from diet have been recognized among the risk factors or, on the other hand, protective agents possibly influencing oxidative stress and pathogenesis of related diseases [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%